Creating Actionable and Insightful Knowledge Applying Graph-CentralityMetrics toMeasure Project Collaborative Performance - Nunes, Marco (2022)
Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.